Razão e experiência na história da natureza da luz para alunos do ensino médio - Gonzaga, Patrícia Ferreira de Souza (2022)
A relevant aspect to understand the Science is the link between rational construction and experimentation. In view of this, we developed and applied an elective course for students whose axis was the history of the nature, presenting as ruptures and reconstructions of thought until the development of the conception of scientific nature. In order to discuss the link between rationality and experience, we use the epistemology of Gaston Bachelard. through the analysis of knowledge of knowledge and carried out in the classroom, we analyze how contemporary activities of content analysis by students on three categories and organize our results: “a phenotechnic”; “the epistemological vector of reason experience”. The results indicate that the approach based on Bachelard's epistemology has the potential to overcome a distorted image of the nature of science. Thus, this work can contribute to discussions on the use of HFCs in teaching, especially for teaching the nature of science.